1993
DOI: 10.1246/bcsj.66.3041
|View full text |Cite
|
Sign up to set email alerts
|

The Structures of Bioactive Cyclodepsipeptides, Beauveriolides I and II, Metabolites of Entomopathogenic Fungi Beauveria sp.

Abstract: Among the cyclodepsipeptides, beauveriolides I (1) and II (2) have been isolated from the mycelium of Beauveria sp., and their stereostructures were elucidated by spectral analyses coupled with syntheses of the corresponding 3-hydroxyoctanoic acid derivatives. Beauveriolide I (1) exhibited moderate insecticidal activities against Spodoptera litura and Callosobruchus chinensis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 5 publications
2
34
0
3
Order By: Relevance
“…[15] The largest group among them, 16 beauverolides, recently attracted interest because of their antiatherogenic activity, as demonstrated by inhibition of acyl-CoA-cholesterol acyltransferase (ACAT). [16] Altogether, the thirteen-membered ring depsipetides cover a wide range of biological activities, including antibiotic, [17] antifungal, [18] insecticidal, [19] and immunosuppressant properties. [20] Like the lydiamycins, none of them are known to display significant cytotoxic activity which is a very common characteristic of larger cyclodepsipetides.…”
Section: O 9 ([M+na]mentioning
confidence: 99%
“…[15] The largest group among them, 16 beauverolides, recently attracted interest because of their antiatherogenic activity, as demonstrated by inhibition of acyl-CoA-cholesterol acyltransferase (ACAT). [16] Altogether, the thirteen-membered ring depsipetides cover a wide range of biological activities, including antibiotic, [17] antifungal, [18] insecticidal, [19] and immunosuppressant properties. [20] Like the lydiamycins, none of them are known to display significant cytotoxic activity which is a very common characteristic of larger cyclodepsipetides.…”
Section: O 9 ([M+na]mentioning
confidence: 99%
“…In this work we used the isolated and most abundant beauveriolide I as a 'standard' 14 and tested separately two different mass spectral techniques with precursor ion selection (PSD MALDI and CID on an ion trap) and in-source CID mass spectra recorded on a sector instrument (APCI). We found that protonated cyclic tetrapeptides, beauverolides, can easily be sequenced by tandem mass spectrometry.…”
Section: Sequencing Of Beauverolides By Tandem Ms (Ms N )mentioning
confidence: 99%
“…Various biological tests have indicated that beauverolides do not exhibit bactericidal, fungicidal or direct insecticidal effects. 13,14 However, they were shown to be apparently involved in insect immunomodulation. 15 macrophage-driven foam cell formation.…”
Section: Introductionmentioning
confidence: 99%
“…By comparison of the sense of optical rotation of 24 (Scheme 4) and ent-24 (Scheme 5), it was revealed that the absolute stereochemistry of C-2 in 24 and 10 was R. In addition, 27 was treated with benzaldehyde dimethyl acetal to produce the cyclic compound 28, and a conventional one-carbon elongation via 29 and 30 afforded primary alcohol 31 as preliminarily reported by the Yamamura group. [20] Protection of the hydroxyl group with tert-butyldimethylsilyl (TBS) or triisopropylsilyl (TIPS) ether, followed by reductive cleavage of the benzylidene acetal, yielded the five-carbon units 34 and 35, respectively. Iodoalkanes 9 and 36 were prepared from 34 and 35 by treatment with I 2 and Ph 3 P, and the product 9 (Scheme 5) was identified by comparison with the former compound 9 derived from aldol syn-16 (Scheme 3); therefore, it can be deduced that C-3 in compounds 9 and 19 also has an R configuration.…”
Section: Introductionmentioning
confidence: 99%